2019
DOI: 10.3389/fmicb.2019.02190
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin-Derived Synthetic Peptide Improves Therapeutic Potential of Vancomycin Against Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa (PA) is the leading cause of corneal blindness worldwide. A constant increase in multi-drug resistant PA strains have heightened the challenge of effectively managing corneal infections with conventional antibiotics. Antimicrobial peptides are promising antibiotic analogs with a unique mode of action. Cathelicidin-derived shorter peptides (FK13 and FK16) have previously been shown to kill a range of pathogens in both in vitro and in vivo systems. Here, our aim was to exploit the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 56 publications
3
43
0
Order By: Relevance
“…Hybridization of this tag sequence to a membrane-lytic short peptide, GNU-7, was shown to improve the antimicrobial efficacy of parent GNU-7 by 16-fold toward P. aeruginosa both in in vitro and in vivo model systems. LPS-targeting GNU-7 variants were also developed through hybridization with lactoferrin (28-34), BPI (84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99), and de novo sequence (125). Chimeric bactericidal peptides targeted to E. faecalis (123) and S. mutans (124) were also developed based on the species-specific pheromones.…”
Section: Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybridization of this tag sequence to a membrane-lytic short peptide, GNU-7, was shown to improve the antimicrobial efficacy of parent GNU-7 by 16-fold toward P. aeruginosa both in in vitro and in vivo model systems. LPS-targeting GNU-7 variants were also developed through hybridization with lactoferrin (28-34), BPI (84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99), and de novo sequence (125). Chimeric bactericidal peptides targeted to E. faecalis (123) and S. mutans (124) were also developed based on the species-specific pheromones.…”
Section: Hybridizationmentioning
confidence: 99%
“…There are also increasing reports examining and exploiting the strategy of using peptide-antibiotic combination to counter AMR, increase the lifespan of conventional antibiotics and HDPs, as well as to reduce the undesired toxicity to host tissues (88,(192)(193)(194). The synergistic effect of peptide-antibiotic combination treatment is likely attributed to the different underlying mechanism of action whereby the membrane perturbation effect of peptides facilitates the passive diffusion of conventional antibiotics into the cells for intracellular targeting action (192).…”
Section: Proposed Strategy In Designing and Developing Hdp-based Treamentioning
confidence: 99%
See 1 more Smart Citation
“…Although many peptides isolated from natural sources have powerful antimicrobial activity, they frequently have certain limitations related to their toxicity against mammalian cells, high production costs and poor stability and/or bioavailability in host physiological conditions [ 14 , 15 ]; synthetic peptides have thus aroused interest. In addition to isolating natural AMPs [ 16 ], synthetic AMPs can be obtained by recombinant expression [ 17 ] or chemical synthesis [ 18 ]; the latter has become popular due to its advantages such as extremely pure products being able to be obtained rapidly and efficiently [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, P. aeruginosa can also form a biofilm, which makes it more difficult to find an effective treatment [6]. Several studies have confirmed that AMPs have killing effects on P. aeruginosa and its biofilm, and may assist in the treatment of antibiotics [8,9]. We have reported the bactericidal effects against P. aeruginosa PA14 (PA14) of hBD3-CBD with in vitro bactericidal test, individual gene expressions, biofilm formation assays, swimming, twitching, and swarming activities [7].…”
mentioning
confidence: 99%